2018
DOI: 10.1051/e3sconf/20186702023
|View full text |Cite
|
Sign up to set email alerts
|

Sythesis of bioavture through hydrodeoxygenation and catalytic cracking from oleic acid using NiMo/Zeolit catalyst

Abstract: Currently, fossil fuels are still the primary source of fuel. As has been known, fossil fuel especially aviation fuel is limited resources and can increase greenhouse gas emissions. This condition encourages replacement efforts of avture into bioavture fuel. In this research, bioavture is synthesized through hydrodeoxygenation and catalytic cracking from oleic acid as a model compound using NiMo/Zeolite catalyst. Hydrodeoxygenation carried out under operating conditions: at temperature of 375°C, under 15 bar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…It means that the catalyst used has a high selectivity to bioavtur, especially those with nickel metal as a promoter. Based on research conducted by Carli et al (2018), the presence of nickel metal in the catalyst structure used in the catalytic cracking process has good selectivity for bioavtur products.…”
Section: Results Of Analysis Of Compoundmentioning
confidence: 99%
“…It means that the catalyst used has a high selectivity to bioavtur, especially those with nickel metal as a promoter. Based on research conducted by Carli et al (2018), the presence of nickel metal in the catalyst structure used in the catalytic cracking process has good selectivity for bioavtur products.…”
Section: Results Of Analysis Of Compoundmentioning
confidence: 99%
“…Setelah dilakukan pengelompokan jenis biofuel berdasarkan rantai hidrokarbonnya, diperoleh data selektivitas katalis terhadap produk biofuel pada Tabel 2 Penggunaan katalis berpenyangga gamma alumina (-Al 2 O 3 ) menghasilkan konversi produk biokerosin (C 12 -C 15 ) yang relatif tinggi namun keberadaan logam nikel (Ni) dalam struktur katalis yang digunakan dapat mempercepat pelepasan produk dari permukaan katalis dan menyebabkan selektivitas terhadap produk biodiesel yang memiliki rantai karbon C 16 -C 20 lebih tinggi [20].…”
Section: Hasil Analisa Komponen Senyawa Produk Biofuelunclassified
“…In the case of zeolite application, Carli et al reported the synthesis of aviation fuel from oleic acid through hydrodeoxygenation reaction of NiMo/zeolite at temperature and pressure conditions were 375 °C and 15 bar, respectively. The catalyst results in the production the aviation fuel, whose yield was up to 36.32% for a 2.5 h reaction time [4]. The above reports indicated that the compounds of aviation fuel could be produced from fatty acid-based compounds, and zeolite can contribute to the reaction as a supported catalyst.…”
Section: ■ Introductionmentioning
confidence: 96%
“…The production was influenced significantly by 3% (wt.%) catalyst loading [2]. Also, other catalysts based on Ni-Mo/SiO 2 and NiMo/zeolite were also reported to increase BAF production and activity [3][4]. In the case of zeolite application, Carli et al reported the synthesis of aviation fuel from oleic acid through hydrodeoxygenation reaction of NiMo/zeolite at temperature and pressure conditions were 375 °C and 15 bar, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation